Mammalian HSP40/DNAJ homologs: cloning of novel cDNAs and a proposal for their classification and nomenclature - Ohtsuka, Kenzo (Cell Stress Society International, 2000)
Abstract We have cloned 10 novel full-length cDNAs of mouse and human HSP40/DNAJ homologs using expressed sequence tag (EST) clones found in the DDBJ/GenBank/EMBL DNA database. In this report, we tentatively designated them mHsp40, mDj3, mDj4, mDj5, mDj6, mDj7, mDj8, hDj9, mDj10, and mDj11. Based on the identity of the deduced amino acid sequences, mHsp40, mDj3, and mDj11 are orthologs of human Hsp40, rat Rdj2, and human Tpr2, respectively. We determined that mDj4 is identical with the recently isolated mouse Mrj (mammalian relative of DnaJ). PSORT analysis (a program that predicts the subcellular localization site of a given protein from its amino acid sequences) revealed that hDj9 has an N-terminal signal peptide; hence, its localization might be extracellular, suggesting that there may be a partner Hsp70 protein that acts together with the hDj9 outside of the cell. The same analysis indicated that mDj7 and mDj10 may have transmembrane domains. In order to simplify the complicated and confusing nomenclature of recently identified mammalian HSP40/DNAJ homologs, we propose here some new rules for their nomenclature. This proposed nomenclature includes the name of species with 2 lowercase letters such as hs (Homo sapiens), mm (Mus musculus) and rn (Rattus norvegicus); Dj standing for DnaJ; the name of types with A, B, and C, which were previously classified as type I, II, and III according to the domain structure of the homologs; and finally Arabic numerals according to the chronological order of registration of the sequence data into the database.